Manajemen Indonesia dan Perbandingannya dengan Negara China dan India - Mahyarni Mahyarni; Astuti Meflinda (Kutubkhanah, 2012)
Management is one of the most central issue throughout an organization or company that wants to continue to exist. Many companies consider the establishment of management is the engine of business. Each companies have some managers in the main position that determine the successful of achieving the goals of it companies. There are so many role in the company that should be roled by the managers so that it is needed the right manager to do it. Good management must role as the circumstances in the company or organization. The Management who cannot do the company’s role will bring the failure.